Use of Lidocaine for Pain Management in the Emergency Medicine: A Systematic Review and Meta-Analysis - Morteza Ghojazadeh; Sarvin Sanaie; Zahra Parsian; Roya Najafizadeh; Hassan Soleimanpour (Tabriz University of Medical Sciences, 2019)
Background: Lidocaine is a well-known medium-acting local anesthetic with a short onset time. It is a valuable drug for managing both acute and chronic pains and is being used as a popular agent for pain control in the emergency department (ED). In this systematic review, we intended to define the effectiveness of lidocaine in pain management of the patients referring to ED. Methods: The preferred reporting items for systematic reviews and meta-analysis (PRISMA) statement was utilized for this Systematic Review (SR). We searched the databases of PubMed, Scopus, ProQuest, and Medline (Ovid) from 1990 to August 2017 for Randomized Controlled Trials (RCTs) in which the study population was referred to the emergency department and received lidocaine. Full-texts of the studies that were published in English were reviewed for inclusion. Both authors individualistically evaluated all studies. Seven articles were eligible for the meta-analysis based on their common outcomes. Results: The total number of subjects was 671. The studies were categorized based on the type of drug and administration route. Mean pain, regardless of the drug administration method, in the placebo group was 0.69 units higher than the lidocaine group. Considering the administration route, mean pain in the placebo group was 0.35 units higher than the lidocaine group when administered topically, and it was lower in the subcutaneous method than the topical method by 1.41 units. Conclusion: Infiltration of lidocaine decreases pain of different procedures in the ED whereas the effect of topical lidocaine is controversial issue.